Pengaruh Jumlah Penduduk, Panjang Jalan dan Pertumbuhan Ekonomi Terhadap Perubahan Lahan Baku Lahan Sawah di Kabupaten/Kota Se-Sumatera - Diva Pandu Artha; Sri Ulfa Sentosa (Universitas Negeri Padang, 2022)
This review makes sense of the degree of the impact between populace, Road Length, Economic Growth on Changes in Raw Land of Paddy Fields in Regencies/Cities all through Sumatra.This concentrate on joins cross segment information in 154 regimes/urban communities with time series from 2019-2020, with the Panel Regression technique with a Random Effect model determination test.the results showed that:(1) Population affects changes in crude land for paddy fields in rules/urban communities all through Sumatra, (2) street length affects changes in crude land for paddy fields in regimes/urban communities all through Sumatra, (3)Economic development affects changes in crude land fields in rules/urban areas all through Sumatra.